Development of a magnetic dispersive micro-solid-phase extraction method based on a deep eutectic solvent as a carrier for the rapid determination of meloxicam in biological samples. Issue 18 (28th April 2020) - Rastbood, Samira; Hadjmohammadi, Mohammad Reza; Majidi, Seyedeh Maedeh
Abstract : An environmentally friendly magnetic dispersive micro solid phase extraction based on a deep eutectic solvent as a carrier and disperser of adsorbents. Abstract : In this study, an environmentally friendly magnetic dispersive micro solid-phase extraction was developed based on a deep eutectic solvent as a carrier and disperser of ferrofluids for the isolation and pre-concentration of meloxicam from biological samples. The extracted analyte was then analyzed by high performance liquid chromatography with ultraviolet detection (HPLC-UV). The ferrofluid was prepared via a combination of silica-coated magnetic nanoparticles and an ethylene glycol/choline chloride deep eutectic solvent as a carrier. In this method, the rapid injection of the magnetic nanoparticles into the sample solution using a green carrier liquid increased the contact surface between the adsorbent and the target analyte which reduced the amount of the adsorbent and extraction time. A fractional factorial design was used for screening some effective parameters such as the amount of SiO2 @Fe3 O4, extraction time, pH of the sample solution, amount of the salt, volume of the desorption solvent, and desorption time. The effective parameters were then optimized by central composite design. Optimized extraction conditions were: amount of SiO2 @Fe3 O4 of 2 mg; extraction time of 1 min; pH of the sample solution of 4; volume of the desorption solvent of 200 μL; and desorption time of 2 min. Under the optimal conditions, wide linear ranges of 5–500 μg L −1 for water and 10–500 μg L −1 were obtained for urine and plasma samples with acceptable extraction recoveries above 89.2%. Limit of detections (LODs) were in the range of 1.5–3.0 μg L −1 . The enrichment factors achieved were above 44.6 with relative standard deviations lower than 6.2%.